2009
DOI: 10.1007/s00420-009-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress experience in young physicians: impact of person- and workplace-related factors

Abstract: OBJECTIVES: The objectives of the present study are to investigate and compare the relative impact of workplace-related factors and personal characteristics on chronic psychosocial stress experience in young physicians. METHODS: In a prospective study, a cohort of Swiss medical school graduates was followed up, beginning in 2001. In their fourth and eighth year after graduation, 443 physicians assessed their workplace conditions, the experienced effort-reward imbalance, the received professional and emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
0
30
0
2
Order By: Relevance
“…Data were gathered by means of an anonymous questionnaire distributed among the participants during identify specific stressful life experiences, though several respondents commented on the relationships with both other professionals as well as patients as a major source of stress. In the case of chronic stress, leading to underperformance [40], high satisfaction with career support, high sense of coherence [34,41], occupational self-efficacy [34], and low values regarding being overcommitted to ones work [35] seem to act as protective factors.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were gathered by means of an anonymous questionnaire distributed among the participants during identify specific stressful life experiences, though several respondents commented on the relationships with both other professionals as well as patients as a major source of stress. In the case of chronic stress, leading to underperformance [40], high satisfaction with career support, high sense of coherence [34,41], occupational self-efficacy [34], and low values regarding being overcommitted to ones work [35] seem to act as protective factors.…”
Section: Participantsmentioning
confidence: 99%
“…Furthermore, as medical doctors are normally seen as a highly resourceful occupational group, often being in charge of their own working situation as well as that of other employees, we may find even less impact of bullying than one would find among other occupational groups. Even more, medical doctors face a range of various, other workplace-related stressors: a diversity of demands, time pressure, long working hours [33], coping with life-threatening situations and compatibility with other demands, e.g., work-home interference [34], which may be as stressful and traumatic as workplace bullying. The proportion of chronically stressed physicians is remarkably consistent over time and amounts up to about 30% of doctors, leading to a reduced health status for those most exposed [35].…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis of differences between 22 factors (e.g., development of health policy, long-term care for patients) were listed and rated on a 5-point Likert scale from 1 "for" to 5 "against." In the Swiss study, no reliability or validity scores were reported [10]. In our study, ratings of 1 and 2 were added and listed as "for" 3 as "neutral," 4 and 5 as "against" for the description of proportions (see Figure 1).…”
Section: Instrumentsmentioning
confidence: 99%
“…Response options were presented on a 5-point Likert scale. For the perception of factors in favor of or against establishing and working in private practice we used the 22 items of the Swiss study [10]. They comprised a preselected number of relevant issues for the topic of establishing and working in private practice and allowed us to compare results internationally.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation